Trends in Learning Innovation in Islamic Religious Education: A Systematic Literature Review - Umami, Novia Rizqiatul; Kambali, Kambali; Arifuddin, Ahmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
ABSTRACTInnovation in Islamic Religious Education learning is the key to creating a more dynamic, interactive, and effective learning experience. Learning innovation is not only limited to the use of technology, but also includes new pedagogical approaches, creative teaching strategies, and the integration of Islamic values with 21st century skills. This study aims to explore various innovation trends in Islamic Religious Education learning, namely learning models and learning media so that they can provide information for Islamic Religious Education teachers to continue to innovate. The research method used in this study is a systematic literature review. In this study, researchers identified, reviewed, reviewed, examined, and presented systematically based on available research. The results of the study showed that of the 19 articles related to learning innovation in Islamic Religious Education in 2019-2024, the Problem Based Learning learning model was the most widely used in Islamic Religious Education learning. The Problem Based Learning learning model encourages students to be directly involved, thus having a positive impact on student learning outcomes. In addition, the learning media that is widely used in Islamic Religious Education learning is audio-visual learning media. The use of audio-visual media can clarify the material being taught, be interesting, and effective in delivering Islamic Religious Education learning materials.Keywords: Learning Innovation, Islamic Religion Education, Systematic Literature Review. ABSTRAKInovasi dalam pembelajaran PAI menjadi kunci untuk menciptakan pengalaman belajar yang lebih dinamis, interaktif, dan efektif. Inovasi pembelajaran tidak hanya terbatas pada penggunaan teknologi, tetapi juga mencakup pendekatan pedagogis baru, strategi pengajaran kreatif, serta integrasi nilai-nilai Islami dengan keterampilan abad 21. Penelitian ini bertujuan untuk mengeksplorasi berbagai tren inovasi dalam pembelajaran PAI, yaitu model pembelajaran dan media pembelajaran sehingga dapat memberikan informasi bagi guru PAI untuk terus berinovasi. Metode penelitian yang digunakan dalam penelitian ini yaitu systematic literature review. Dalam penelitian ini, peneliti mengidentifikasi, meninjau, menelaah, mereview, memeriksa, dan memaparkan secara sistematis berdasarkan penelitian yang tersedia. Hasil penelitian menujukkan bahwa dari 19 artikel terkait inovasi pembelajaran pada Pendidikan agama islam pada tahun 2019-2024, model pembelajaran Problem Based Learning paling banyak digunakan dalam pembelajaran PAI. Model pembelajaran Problem Based Learning mendorong siswa untuk terlibat secara langsung, sehingga memberikan dampak positif terhadap hasil belajar siswa. Selain itu, media pembelajaran yang banyak digunakan dalam pembelajaran PAI yaitu media pembelajaran audio visual. Penggunaan media audio visual tersebut dapat memperjelas materi yang diajarkan, menarik, dan efektif untuk menyampaikan materi pembelajaran PAI.Kata kunci: Inovasi Pembelajaran, Pendidikan Agama Islam, Systematic literature review.